Pengenalan Dasar-Dasar Bahasa Inggris pada Tingkat Sekolah Dasar di Merauke - Pertiwi, Sri Ananda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
Finding students in Merauke who still do not understand the basic English, starting from elementary to university students is common. Considering the urgency of mastering English nowadays, the introduction of English recommended form the early age. The preliminary observation at an elementary school revealed that many students were unfamiliar with English. This is the background for the author to conduct this community service, namely the introducing the basics English to students of elementary schools in Merauke. This activity involved two class of grade 4 and 2 teachers in one of elementary schools in Merauke. The stages in this activity, carrying out interview for teachers, observation, pre-test, teaching, post-test and interview for students. From the results it was found that students had a positive attitude in learning English, such as being active, enthusiastic and interested in learning English during the learning process and be able to understand the material well. No human resources capable of teaching English is the challenge faced by the school.